An architecture for translational cancer research as exemplified by the German Cancer Consortium - Lablans, Martin; Schmidt, Esther E.; Ückert, Frank (JCO clinical cancer informatics, 2018)
Networking of medical institutions by means of a capable data infrastructure has the potential to open up vast amounts of routine data to translational cancer research. However, the secondary use of information collected independently in several institutions is a challenging task of data integration. In this review, we discuss the requirements and common challenges involved in the establishment of such a platform. We present methods and tools from the field of medical informatics as solutions to semantic and technical heterogeneity, questions of data protection and record linkage, as well as issues of trust and data ownership. We also describe the architecture of an existing cancer research network as an exemplary application of these methods.
Published online 16 February 2018
Gesehen am 20.06.2018